FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN OPINI GOING CONCERN AUDITOR PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Triyana Arni Agustina; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to analyze factors that affect auditor’s propensity to issue a going concern opinion. The examined factors of this research are auditor’s going concern opinion as dependent variable and 8 of independent variable are audit firms, prior year’s opinion auditor, current ratio, Cash flow adequacy, debt default, size, audit lag, recurring loss from operations indicator. The samples consist of companies listed on Indonesian Stock Exchange (IDX) and having Z Score between 1,81 until 2,99 This measures developed by Altman model. Total sampel of this research are 58 listed company with research years 2006 – 2008. This research is carried out by doing content analysis on corporation annual report and is tested by regression. The result of this research shows that audit firms scale, from the Big 4 and non the Big 4, that no have positif affect for auditor to issue a going concern opinion. The significant affect are prior year’s opinion auditor and size company. The other independent variables no have significant affect for auditor to issue a going concern opinion.